Impact of route and adequacy of nutritional intake on outcomes of allogeneic haematopoietic cell transplantation for haematologic malignancies. Issue 2 (April 2019) - Beckerson, Julie; Szydlo, Richard M.; Hickson, Mary; Mactier, Catriona E.; Innes, Andrew J.; Gabriel, Ian H.; Palanicawandar, Renuka; Kanfer, Edward J.; Macdonald, Donald H.; Milojkovic, Dragana; Rahemtulla, Amin; Chaidos, Aristeidis; et al.
Summary: Background: Allogeneic haematopoietic cell transplantation (HCT) is often associated with poor oral intake due to painful mucositis and gastrointestinal sequalae that occur following a preparative regimen of intensive chemotherapy and/or total body radiation. Although attractive to assume that optimal nutrition improves HCT outcomes, there are limited data to support this. It is also unclear whether artificial nutrition support should be provided as enteral tube feeding or parenteral nutrition (PN). Methods: We analysed day-100 non-relapse mortality (NRM), incidence of acute graft-versus-host disease (GvHD), acute gastrointestinal GvHD, 5-year survival and GvHD-free/relapse-free survival (GRFS) according to both route and adequacy of nutritional intake prior to neutrophil engraftment, together with other known prognostic factors, in a retrospective cohort of 484 patients who underwent allogeneic HCT for haematologic malignancy between 2000 and 2014. Results: Multivariate analyses showed increased NRM with inadequate nutrition (hazard ratio (HR) 4.1; 95% confidence interval (CI) 2.2–7.2) and adequate PN (HR 2.9; 95% CI 1.6–5.4) compared to adequate enteral nutrition (EN) both P  < .001. There were increased incidences of gastrointestinal GvHD of any stage and all GvHD ≥ grade 2 in patients who received PN (odds ratio (OR) 2.0; 95% CI 1.2–3.3; P  = .006, and OR 1.8; 95% CI 1.1–3.0; P  = .018, respectively), compared to adequate EN. Patients who received adequate PN and inadequate nutrition also had reduced probabilities of survival and GRFS at 5 years. Conclusion: Adequate EN during the early transplantation course is associated with reduced NRM, improved survival and GRFS at 5 years. Furthermore, adequate EN is associated with lower incidence of overall and gut acute GvHD than PN, perhaps because of its ability to maintain mucosal integrity, modulate the immune response to intensive chemo/radiotherapy and support the gastrointestinal tract environment, including gut microflora.